Requisito di distinzione ed esigenza di prossimità. La concezione husserliana dell’empatia come base dell’intersoggettività trascendentale - Besoli, Stefano (Bollettino Filosofico, 2022)
In this essay my aim is to defend the Husserlian account of empathy. The problerm of the other is the touchstone of transcendental phenomenology and I shall argue that the account Husserl provides in the fifth chapter of Cartesian Meditations is both schematically sound and methodological fruitful. The philosophic problem of other is particularly acute for Husserl because the aim of his inquiry requires its solution yet the procedure he employs appears to preclude. By analyzing the evolution of the entire Husserlian problem of empathy and, in parallel, the extension of the reduction to intersubjectivity, it was intended to show that whatever the content of empathy, Husserl has reached his philosophical goal: to disclose its foundation and to articulate its invariant eidetic structure. Keywords: Analogical Apperception, Appresentation, Empathy, Husserl, Phenomenology